Organized crime and terrorist networks - Ruggiero, Vincenzo (Routledge studies in crime and society, 2020)
"This book explores organized crime and terror networks and the points at which they intersect. It analyzes the close relationships between these criminalities, the prevalence and ambiguity of this nexus, the technological elements facilitating it, and the financial aspects embedded in this criminal partnership"--